Budget and Current Account Deficits in SEACEN Countries: Evidence Based on the Panel Approach - Ahmad Zubaidi, Baharumshah; Evan, Lau (Örebro University School of Business, 2005)
In this paper, the twin deficits hypothesis was examined using data of nine SEACEN countries. To compensate for the lack of time series observations, data was polled from the nine countries into one panel. The effects of interest rate and exchange rate in the causal chain between budget and current account deficits were stressed. At the empirical level, there is enough evidence to support the view that Asian budget deficit causes current account deficit directly as well as indirectly. From the policy perspective, the statistical analysis suggests that managing budget deficit offers scope for improvement in the current account deficit. However, this finding does not support the policy of manipulating the intermediate variables to reduce the twin deficits to a sustainable level since these variables appear to be endogenous in the system.